2022
DOI: 10.1002/smll.202203222
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Polysulfide Conversion Kinetics Using Tungsten Diboride as Additive For High‐Performance Li–S Battery

Abstract: The practical application of Li–S batteries is severely limited due to low sulfur utilization, sluggish sulfur redox kinetics, intermediate polysulfide dissolution/shuttling, and subsequent anode degradation. A smart cathode with efficient electrocatalyst and a protected anode is necessary. Herein, hollow carbon (HC) spheres are used as a sulfur host to improve the electrical conductivity and buffer the volume expansion of active materials. Considering the weak interaction between carbon and lithium polysulfid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…6(a). The calculation route of the sulfur reduction reaction refers to the previous report, [50][51][52][53][54] and our calculation results are basically consistent with the trend in these references: except that the last reduction step (Li 2 S 2 -Li 2 S) is an endothermic process, the rest of the elementary steps are exothermic, implying that the last reduction step is the rate-limiting step of the overall SRR. The endothermic reaction of the Li 2 S 2 -Li 2 S step is attributed to the intractable solid-state reaction, which is basically consistent with those reported in other literature reports.…”
Section: Catalytic Performance Of the Heterostructuressupporting
confidence: 91%
“…6(a). The calculation route of the sulfur reduction reaction refers to the previous report, [50][51][52][53][54] and our calculation results are basically consistent with the trend in these references: except that the last reduction step (Li 2 S 2 -Li 2 S) is an endothermic process, the rest of the elementary steps are exothermic, implying that the last reduction step is the rate-limiting step of the overall SRR. The endothermic reaction of the Li 2 S 2 -Li 2 S step is attributed to the intractable solid-state reaction, which is basically consistent with those reported in other literature reports.…”
Section: Catalytic Performance Of the Heterostructuressupporting
confidence: 91%
“…The high polysulde rejection was attributed to the electrophilic boron centers in the COF that easily adsorbed the polysuldes. Work by Sahu et al 291 has also shown the efficacy of boron atoms as adsorptive centers for sulfur. Moreover, the small 1.2 nm pore sizes sieved the large polysuldes while allowing high Li diffusion.…”
Section: Covalent-organic Framework (Cof)mentioning
confidence: 97%
“…AlB 2 -type metal borides are primarily ionic layered materials, where adjacent layers are held together by ionic bonding. , This structure gives rise to a number of interesting properties, including ultrahigh strength, good electrical and thermal conductivity, wear resistance, chemical inertness, and high melting point. , MgB 2 , the flagship member of the metal diboride family, is known for its superconductivity, TiB 2 is known for its use in ballistic armors, and AlB 2 has been used as a reinforcing material. , However, they are recently being revisited in multiple new domains due to their excellent electrochemical properties. One of the earliest reports highlighted the investigation of various metal diborides such as AlB 2 , CrB 2 , HfB 2 , MgB 2 , NbB 2 , TaB 2 , TiB 2 , VB 2 , and ZrB 2 as potential catalysts for HER, VB 2 and WB 2 for batteries, and MgB 2 for water splitting and lithium-ion batteries. ,, Research trends in the synthesis of metal diborides encompass various methods including the solid-state reaction method, sol–gel synthesis, mechanical alloying, and self-propagating high-temperature synthesis (SHS). These techniques allow for precise control over material properties, microstructure, and phase composition, offering tailored metal diborides for specific applications.…”
Section: Research Trends In Alb2-type Metal Diborides and Xbenesmentioning
confidence: 99%